TRP Channels as Emerging Therapeutic Targets for Neurodegenerative Diseases - Hong, Chansik; Jeong, Byeongseok; Park, Hyung Joon; Chung, Ji Yeon; Lee, Jung Eun; Kim, Jinsung; Shin, Young-Cheul; So, Insuk (Frontiers in Physiology, 2020)
The development of treatment for neurodegenerative diseases (NDs) such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, and amyotrophic lateral sclerosis is facing medical challenges against the increasing aging population. However, some pharmaceutical companies have ceased development of therapeutics for NDs, and no new treatments for NDs have been established during the last decade. The relationship between ND pathogenesis and risk factors has not been completely elucidated. Herein, we review the potential involvement of transient receptor potential (TRP) channels in NDs, where oxidative stress and disrupted Ca2+ homeostasis consequently lead to neuronal apoptosis. Reactive oxygen species (ROS)-sensitive TRP channels can be key risk factors as polymodal sensors, since progressive late onset with secondary pathological damage after initial toxic insult is one of the typical characteristics of NDs. Recent evidence indicates that the dysregulation of TRP channels is a missing link between disruption of Ca2+ homeostasis and neuronal loss in NDs. In this review, we discuss the latest findings regarding TRP channels to provide insights into the research and quests for alternative therapeutic candidates for NDs. As the structures of TRP channels have recently been revealed by cryo-electron microscopy, it is necessary to develop a new TRP channel antagonists and reevaluate existing drugs.